2017
DOI: 10.2147/imcrj.s147177
|View full text |Cite
|
Sign up to set email alerts
|

Left-sided incarcerated Amyand’s hernia with cecum and terminal ileum: a case report

Abstract: BackgroundAmyand’s hernia, which is the presence of a normal or pathological appendix as a part of an inguinal hernia, is a rare clinical entity. We are reporting a very rare case of left-sided incarcerated Amyand’s hernia with cecum and terminal ileum involvement.Case presentationA 4-year-old male child with left inguinal swelling of 2-year duration presented to Goba Referral Hospital. Two days before the patient visited our hospital, the swelling had become irreducible and caused severe groin pain. He had ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Left sided presentation is possible but rarely reported. 8,9 Till 2014, only seven patients with left sided presentation had been reported in English Literature. 10 These maybe associated with situs inversus, intestinal malrotation and extremely mobile cecum.…”
Section: Discussionmentioning
confidence: 99%
“…Left sided presentation is possible but rarely reported. 8,9 Till 2014, only seven patients with left sided presentation had been reported in English Literature. 10 These maybe associated with situs inversus, intestinal malrotation and extremely mobile cecum.…”
Section: Discussionmentioning
confidence: 99%
“…Since then hernia with vermiform appendix as content is termed as 'Amyand's hernia'. 3,4 According to previous study amongst all Amyands hernia inflamed appendix found in 0.1 % cases. 4,6 Incident of Amyands hernia is 3 times higher in childrens than in adult population due to patent processus vaginalis.…”
Section: Introductionmentioning
confidence: 92%
“…3,4 According to previous study amongst all Amyands hernia inflamed appendix found in 0.1 % cases. 4,6 Incident of Amyands hernia is 3 times higher in childrens than in adult population due to patent processus vaginalis. 5 Apart from this most commonly Amynads hernia occurred on right side because of two reasons, one normal anatomical site of appendix and second right sided inguinal hernias are more common than left.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Amyand’s hernia was common to present on the right side based on the appendix vermiform position but in a rare condition, it could find in the left-side. Left-side Amyand’s hernia could be associated with situs inversus, intestinal malrotation, and mobile caecum [ 4 ].…”
Section: Introductionmentioning
confidence: 99%